Radiative neutron capture rate of 19N(n, γ)20N. (December 2020) - Singh, G.; Shubhchintak,; Dan, M.; Chatterjee, R.
Abstract: Low and medium mass neutron rich nuclei have been thought of as important constituents in the final abundance patterns resulting from the r-process reaction network calculations. However, a direct study of these nuclei is extremely difficult and indirect methods like Coulomb dissociation are used for their investigation. We calculate the reaction rate of the 19 N(n, γ) 20 N radiative capture reaction using Coulomb dissociation of the medium mass exotic nucleus 20 N, under the aegis of finite range distorted wave Born approximation theory and compare our results with those from the experiment. The reaction rate, when included in the full reaction network, is thought to be crucial to the final abundance of Fluorine isotopes.